Students’ motivation in an online and a face-to-face semester: a comparison of initial level, development, and use of learning activities - Bosch, Eva; Spinath, Birgit (Zeitschrift für Psychologie, 2023)
: Challenges for university students were high during distance education in lockdowns due to the COVID-19 pandemic. Self-regulation and motivation became more important, but motivation was possibly challenged more. To investigate motivational differences and possible positive effects of evidence-based learning activities, we followed two cohorts of preservice teachers over the course of one semester: One cohort was followed in 2019 in a face-to-face semester (N2019 = 225), and another cohort was followed 1 year later during the first lockdown (N2020 = 311). Students indicated their motivation at five measurement occasions and reported their use of learning activities twice. Multigroup linear change models indicated an overall decline of motivation in both cohorts. Surprisingly, neither initial motivation level nor motivational change differed between cohorts. Students who used more learning activities reported a more positive motivational development. This highlights the chance of evidence-based learning activities for students’ motivation in regular and distance education.